Distress Tolerance and Perceived Barriers to Smoking Cessation. Issue 3 (July 2013) - Kraemer, Kristen M.; McLeish, Alison C.; Jeffries, Emily R.; Avallone, Kimberly M.; Luberto, Christina M.
Background: The present study examined the role of emotional distress tolerance (DT) in predicting barriers to smoking cessation and number of quit attempts. Methods: The sample consisted of regular daily smokers ( N = 126; 37 females; M age = 36.51, SD = 13.05) who completed self-report measures on affect and smoking. Results: After controlling for daily smoking rate and anxiety sensitivity, emotional DT significantly predicted internal barriers to cessation (6.9% unique variance) but not external or addiction-related barriers to cessation. Inconsistent with prediction, emotional DT did not significantly predict number of quit attempts. Conclusions: These results suggest that individuals who are low in emotional DT believe that quitting smoking will be difficult because it takes away an important affect regulation strategy, and there may be utility in targeting emotional DT in smoking cessation interventions.